Movement-related pain as a learned response: an investigation of the possible mechanisms underlyng movement-related pain persistence and recovery in subjects with chronic musculoskeletal pain - Alaiti, Rafael Krasic (2021)
Although our understanding about pain neurobiology have increased over the last decades, there is still a gap of knowledge regarding the understanding of the mechanisms associated with pain persistence and the mechanisms of action of interventions for subjects with chronic musculoskeletal pain. The main focus of this thesis was to discuss in depth the possible underlying mechanisms associated with pain persistence and recovery in an effort to contribute to the bridging of this gap of knowledge throught four researchs. The first three studies investigated assumptions of current hypothesis about pain persistence through the lens of learning theories, by verifyng if (1) pain can be conditioned to movements through associative learning; (2) investigating which factors were associated with pain distribution through movements and daily activities commonly reported as painful by subjects with chronic pain; and by (3) investigating if chronic musculoskeletal pain is associated with perceptual distortions in other perceptual continuums associated with movements that could foster avoidance behaviors. The last study of this thesis was (4) a systematic review that aimed to systematically identify and synthesise studies that conducted mediation analyses of randomized controlled trials that test or estimate indirect effects of cognitive-behavioral and exercise-based interventions for pain and disability in people with chronic musculoskeletal pain. The basis for the conduction of these studies, as well as its main findings were discussed throughout this thesis